2019
DOI: 10.1007/s13197-019-03741-6
|View full text |Cite
|
Sign up to set email alerts
|

Quality of shredded carrots minimally processed by different dipping solutions

Abstract: The whiteness of shredded carrots is generally caused by enzymatic reactions after removal of natural protection during the minimal processing. Moreover, the use of chlorinated solution in sanitizing step of processing, promotes the formation of halogenated by-products, with correlated environmental and health risks in processing areas. This study investigated the effect of different acidic solutions on the quality of shredded carrots during the storage at two refrigerated temperatures (4°C and 7°C), as altern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Generally, cantaloupes had lower POD activity as compared to the other uncoated samples (day 0) regardless of treatments. This could be due to the low O 2 level developed in the fruit coatings [39]; and the possible reduction of carotene which can be one of the important factors of POD activity [40]. On the other hand, CH/TiO 2 /TT samples had higher POD activity as compared to other samples during storage.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, cantaloupes had lower POD activity as compared to the other uncoated samples (day 0) regardless of treatments. This could be due to the low O 2 level developed in the fruit coatings [39]; and the possible reduction of carotene which can be one of the important factors of POD activity [40]. On the other hand, CH/TiO 2 /TT samples had higher POD activity as compared to other samples during storage.…”
Section: Discussionmentioning
confidence: 99%
“…Another study indicated that treatment with AsA inhibited the reduction of the sugars content in strawberry fruit during cold storage [ 58 ]. This result could be due to the reduction of PAL activity by AsA treatment resulting in a lower loss of sugars during storage [ 59 ]. Total sugar preservation in samples treated with either PMO or TTO could be explained by the role of EOs in reducing the activity of enzymes that convert starch to sugar in stored crops [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some differences in the safety of using chlorine‐based compounds have been discussed due to their limited effect on microbial control and their possible production of chlorinated organic compounds. The reactions of chlorine with organic matter lead to the formation of carcinogenic and mutagenic byproducts, requiring more rigorous process control (Coroneo et al, 2017; Piscopo et al, 2019). Thus, research on alternative sanitizers to chlorine and other methods for pathogen control has been conducted with the objective of developing effective preservation technologies and ensuring the production of safe foods (Zudaire et al, 2018).…”
Section: Chemical Preservation Methodsmentioning
confidence: 99%
“…It is effective at concentrations between 50 and 350 ppm. It is traditionally used for washing vegetables in aqueous solutions such as sodium hypochlorite (NaClO), sodium chlorite (NaClO 2 ), and chlorine dioxide (ClO 2 ) (Feliziani et al, 2016;Piscopo et al, 2019).…”
Section: Chlorinementioning
confidence: 99%